2017
DOI: 10.18632/oncotarget.22587
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of the antiparasitic agent ivermectin via inhibition of Yes-associated protein 1 expression in gastric cancer

Abstract: Yes-associated protein 1 (YAP1) acts as an oncogene through dephosphorylation and nuclear translocation, and nuclear accumulation of YAP1 is associated with poor prognosis in gastric cancer (GC). We previously identified ivermectin, an antiparasitic drug, as a YAP1 inhibitor. Here, we aimed to clarify whether ivermectin had antitumor effects on GC through inhibition of YAP1. First, we evaluated the antiproliferative effects of ivermectin on human GC cells using in vitro proliferation assays and a xenograft mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 26 publications
(27 reference statements)
0
27
0
Order By: Relevance
“…. Immunohistochemical analysis of KIF15 expression was performed with formalin-fixed paraffinembedded surgical sections (FFPE) obtained from patients with HCC, or a HCC cell line (HepG2) or healthy donor PBMC, as previously described (21,26). Primary rabbit polyclonal antibody against KIF15 (ab90735; Abcam) was used at a dilution of 1:200.…”
Section: Immunohistochemical Analysis (Ihc)mentioning
confidence: 99%
“…. Immunohistochemical analysis of KIF15 expression was performed with formalin-fixed paraffinembedded surgical sections (FFPE) obtained from patients with HCC, or a HCC cell line (HepG2) or healthy donor PBMC, as previously described (21,26). Primary rabbit polyclonal antibody against KIF15 (ab90735; Abcam) was used at a dilution of 1:200.…”
Section: Immunohistochemical Analysis (Ihc)mentioning
confidence: 99%
“…In the past year, more than one million patients with gastric cancer have been diagnosed worldwide [ 38 ]. Nambara’s study showed that IVM could significantly inhibit the proliferation of gastric cancer cells in vivo and in vitro and that the inhibitory effect of IVM depended on the expression of Yes-associated protein 1(YAP1)[ 39 ]. The gastric cancer cell lines MKN1 and SH-10-TC have higher YAP1 expression than MKN7 and MKN28 cells, so MKN1 and SH-10-TC cells are sensitive to IVM, while MKN7 and MKN28 are not sensitive to IVM.YAP1 plays an oncogenic role in tumorigenesis, indicating the possibility of the use of IVM as a YAP1 inhibitor for cancer treatment [ 40 ].…”
Section: The Role Of Ivm In Different Cancersmentioning
confidence: 99%
“…Notably, however, the administration of dasatinib as a single-agent was not effective as a second-line treatment for MM during a recent phase II trial [ 16 ]; likewise, administration of dasatinib as a neoadjuvant treatment was not shown to confer any benefit to patients with MPM. In contrast, a recent study reported the ability of the anti-parasitic agent ivermectin to inhibit YAP1, and thereby exert significant effects on gastric cancer [ 134 ], hepatocellular carcinoma, and MM cells [ 130 ].…”
Section: Therapeutic Applications Based On Hippo Pathway Dysregulamentioning
confidence: 99%